2018
DOI: 10.1186/s12870-018-1471-6
|View full text |Cite
|
Sign up to set email alerts
|

An improved suppression subtractive hybridization technique to develop species-specific repetitive sequences from Erianthus arundinaceus (Saccharum complex)

Abstract: BackgroundSugarcane has recently attracted increased attention for its potential as a source of bioethanol and methane. However, a narrow genetic base has limited germplasm enhancement of sugarcane. Erianthus arundinaceus is an important wild genetic resource that has many excellent traits for improving cultivated sugarcane via wide hybridization. Species-specific repetitive sequences are useful for identifying genome components and investigating chromosome inheritance in noblization between sugarcane and E. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…hybrids ) varieties are the hybrids of S. officinarum and S. spontaneum , in which S. spontaneum is the wild type parent and a highly versatile species with many phenotypes, capable of growing under different biotic and abiotic stress conditions. S. spontaneum is a source of resistance genes such as cold, drought, salinity, high, and low temperature tolerance (Yang et al, 2020; Yu et al, 2018). Salt stress affects sugarcane in two different phases.…”
Section: Introductionmentioning
confidence: 99%
“…hybrids ) varieties are the hybrids of S. officinarum and S. spontaneum , in which S. spontaneum is the wild type parent and a highly versatile species with many phenotypes, capable of growing under different biotic and abiotic stress conditions. S. spontaneum is a source of resistance genes such as cold, drought, salinity, high, and low temperature tolerance (Yang et al, 2020; Yu et al, 2018). Salt stress affects sugarcane in two different phases.…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive DNA probes are the FISH probes used widely in plant genome research, however, such probes always show a varied signal among different species as a result of the instability of genome, so that they cannot be used for cytogenetics research [22]. In T. arundinaceum, Yu et al [23] screened many repetitive sequences; unfortunately, these repeats showed a diversity site that cannot be used as a stable marker for chromosome identification. By comparison, recently, the FISH probe based on single copy sequences designed from genome sequences has provided us a more universal and stable marker for cytological study in plants [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional methods, SSH offers a simple, rapid, and affordable high-throughput screening method for separating DNA sequences that distinguish two closely related species. Although SSH only has been applied successfully to separate species-speci c sequences in a few plants, this method had already proved to be capable of screening out a reservoir of species-speci c molecular markers (Ge et al 2012;Li et al 2004;Yu et al 2018). Notably, accurate identi cation of putative progeny hinges on the adequate molecular markers covering the whole genome.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, accurate identi cation of putative progeny hinges on the adequate molecular markers covering the whole genome. In SSH array, the e cient ampli cation of species-speci c sequences by PCR is thank to that those short and high copy number fragments tend to be ampli ed in preference to larger and lower copy number ones (Yu et al 2018). Highcopy-number repetitive sequences comprise most eukaryotic genomes where they are major contributors to genome evolution (Heslop-Harrison and Schwarzacher 2011; Naito et al 2009).…”
Section: Discussionmentioning
confidence: 99%